2002
DOI: 10.1164/rccm.200204-289oc
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Nicotine Exposure Blunts the Cardiorespiratory Response to Hypoxia in Lambs

Abstract: Because smoking during pregnancy is a major risk factor for late fetal death and the sudden infant death syndrome, we investigated cardiorespiratory defense mechanisms to hypoxia in 7 prenatally nicotine-exposed (N) lambs (approximate maternal dose: 0.5 mg/kg/day) and 11 control (C) lambs all at an average age of 5 days. The ventilatory response to 10% oxygen (hyperpnea) was significantly attenuated during quiet sleep in N lambs compared with C lambs and in N lambs aroused from sleep later compared with C lamb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
62
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 92 publications
(71 citation statements)
references
References 49 publications
8
62
1
Order By: Relevance
“…Additionally, the cardiovascular response to hypoxia was lower in the exposed group. The maternal plasma level induced by this dose is lower than what is observed in pregnant habitual smokers (Hafstrom et al, 2002).…”
Section: Mechanismscontrasting
confidence: 58%
See 3 more Smart Citations
“…Additionally, the cardiovascular response to hypoxia was lower in the exposed group. The maternal plasma level induced by this dose is lower than what is observed in pregnant habitual smokers (Hafstrom et al, 2002).…”
Section: Mechanismscontrasting
confidence: 58%
“…The lack of mortality at a 2 mg/kg/day dose, however, does not imply a lack of effect on developing organ systems at lower doses. Hafstrom et al (2002) observed that time from onset of hypoxia to arousal from sleep was significantly longer in exposed lambs than in controls, when nicotine exposure occurred at 0.5 mg/kg/day during the last 49 days of gestation. Additionally, the cardiovascular response to hypoxia was lower in the exposed group.…”
Section: Mechanismsmentioning
confidence: 89%
See 2 more Smart Citations
“…Prenatal nicotine exposure also delays arouse from sleep. These results suggest that prenatal nicotine exposure blunts major elements of the cardiorespiratory defense to hypoxia [112] .…”
Section: Effects Of Perinatal Nicotine Exposure On Neonatal Respiratomentioning
confidence: 78%